Analisis Persepsi Keselamatan Perjalanan Kereta Api Terhadap Stres Kerja Masinis Di Stasiun Tugu Yogyakarta - Damayanti, Ajeng Tyas (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
The availability of qualified human resources will affect the safety of rail travel. Guaranteed safety of this trip materialized from the minimum number of train accidents that occurred. In identifying the causes of train accidents, the human error factor is largely the main cause. This is what causes human resources to become an important concern in the operation of trains. Data were collected by using questionnaires consisting of perception questionnaire on railway safety and work stress. Interviews were used to complete the questionnaire results. Data analysis was done by regression analysis to know the influence of safety perception to work stress. The results showed that 77% of the respondents had low safety perception, while the other 23% had high perception of safety. As many as 70% of machinists have high work stress, while 30% have low work stress. Safety perception proved to be related to work stress experienced by machinist. This is indicated by a variable of -, 338 which states that the relationship between perception of safety proved to have a relationship with job stress of 0.338 with a negative relationship. This relationship analysis is evidenced by Pearson Correlation. Regression analysis obtained correlation coefficient of 0.114 which states that 11.4% work stress is influenced by the perception of safety